A procedural check list for pleural decompression and intercostal catheter insertion for adult major trauma. Issue 1 (January 2015) - Anderson, M.; Fitzgerald, M.; Martin, K.; Santamaria, M.; Arendse, S.; O'Reilly, G.; Smit, de V.; Orda, U.; Marasco, S.
Abstract: Background: Intercostal catheter (ICC) insertion is the standard pleural decompression and drainage technique for blunt and penetrating traumatic injury. Potentially high complication rates are associated with the procedure, with the literature quoting over 20% in some cases (1–4). Empyema in particular is a serious complication. Risk adverse industries such as the airline industry and military services regularly employ checklists to standardise performance and decrease human errors. The use of checklists in medical practice is exemplified by introduction of the WHO Surgical Safety checklist. Methods: The Alfred Hospital in Melbourne, Australia is an Adult Level 1 Trauma Centre. In August 2009 The Alfred Trauma Service introduced an evidence-based checklist system for the insertion of ICCs, combined with standardised formal training for resident medical staff, in an attempt to minimise the incidence of ICC related empyema. Results: Between January 2003 and July 2009 the incidence of empyema was 1.44% (29 in 2009 insertions). This decreased to 0.57% between August 2009 and December 2011 (6 in 1060 insertions) when the measures described above were introduced [ p = 0.038 Fisher's exact test, 2-tailed]. Conclusion: Quality control checklists – such as the ICC checklist described – are a sensible and functional means to standardise practice, to decrease procedural error and to reduce complication rates during trauma resuscitation.